Comparative analysis offemale charactersin the novelsCaoXuechin «Dream of the Red Chamber » and M. Auezov «Abai’s Way» - Kenzhebaeva, А A; Kenzhebaeva, L A (Journal of Oriental Studies, 2016)
This article discusses acomparative analysis offemale charactersin the novelsCaoXuechin «Dream of the Red Chamber» and M.Auezov»Abai’s Way». Comparetiveanalyzethe components ofthe unit-Onimtaken from thework ofCaoXuechin»Dream of the Red Chamber» and M.Auezov»Abai’s Way».These fragmentsstudies showthe specificity ofimagesof female characters in Chinese and Kazakh literaturethat reflect theparticularworldviewof storage medialanguages.